International business : managing globalization - Hill, John S., 1951- (Los Angeles : SAGE, 2009)
'Reflecting a strong managerial orientation, a corporate emphasis, and a true global-local focus, International Business: Managing Globalization explains the whats and whys of global differences as it covers industries, competitors, regions, and markets from the perspectives of practicing managers. Author John S. Hill reviews the geographic and historic backgrounds of regions and markets in a way that no other text has done, with special focus on global supply chains, global branding, and world religions as they affect management at the local level.'--Jacket.
Includes bibliographical references and index.
Keywords: Globalization -- Economic aspects; International business enterprises -- Management; International economic integration; International business enterprises